2001
DOI: 10.1021/jm015509z
|View full text |Cite
|
Sign up to set email alerts
|

A Rational Approach to the Design of Selective Substrates and Potent Nontransportable Inhibitors of the Excitatory Amino Acid Transporter EAAC1 (EAAT3). New Glutamate and Aspartate Analogues as Potential Neuroprotective Agents

Abstract: Two three-dimensional receptor interaction models for EAAT substrates and nontransportable inhibitors have been developed, and new glutamate (Glu) and aspartate (Asp) analogues have been synthesized. The analogues 1a and 3 represent novel lead compounds for the development of EAAT substrates and nontransportable inhibitors, selective for EAATs over iGluRs, as possible neuroprotective agents useful to minimize the progression of chronic or acute neurodegenerative diseases. The role played by the protonatable am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…A major distinction between L-TBOA and WAY-213613 is the conformity of the former to all features with the exception of the hydrophobic center 4.11, whereas WAY-213613 fits all features with the exception of the hydrogen bond acceptor. We find that the newly described inhibitors presented in the current study lack a distal acidic group identified by others (Campiani et al, 2001(Campiani et al, , 2003 as an important pharmacophoric site corresponding to the hydrogen bond acceptor feature in our model. Moreover, the compounds reported in the current study share in common the distal hydrophobic center 4.11.…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…A major distinction between L-TBOA and WAY-213613 is the conformity of the former to all features with the exception of the hydrophobic center 4.11, whereas WAY-213613 fits all features with the exception of the hydrogen bond acceptor. We find that the newly described inhibitors presented in the current study lack a distal acidic group identified by others (Campiani et al, 2001(Campiani et al, , 2003 as an important pharmacophoric site corresponding to the hydrogen bond acceptor feature in our model. Moreover, the compounds reported in the current study share in common the distal hydrophobic center 4.11.…”
Section: Resultssupporting
confidence: 49%
“…It is important to note that in the current model, the folded form of the aspartate framework in TBOA is wellsuperimposed with the folded form of glutamate (Fig. 9), whereas others have proposed the extended form for the aspartate framework in their model (Koch et al, 1999;Campiani et al, 2001Campiani et al, , 2003. Each of these approaches has used different modeling scenarios, and although we have predicted the folded form of the aspartate framework, the other features of the molecule present a very similar configuration in all modeling studies.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…6A, left panel). This outward current was caused by inhibition of the sustained leak anion conductance of EAAC1 in the presence of intracellular SCN − (19,31). However, TBOA did not inhibit the inward anion current generated by 500 μM alanine (Fig.…”
Section: Properties Of Mixed Eaac1 Wt -Eaac1 R446qmentioning
confidence: 92%
“…As pointed out earlier, there has been a wealth of information on the substrate specificity and structural requirements of GluT 19,26,34,[92][93][94][95][96][97][98][99][100][101]103,105,[107][108][109] even in relation to individual EAAT's 110,112,114,[179][180][181][182][183] yet this structure-activity data has not so far been satisfactorily matched with the protein architecture of the putative substrate-binding regions. Moreover, some of the EAAT's may form multimeric complexes 184) and most of them also act as chloride channels 185) ; for a review see ref.…”
Section: Unresolved Problems and Future Direc-tionsmentioning
confidence: 99%